Numerical Approach of Linear Volterra Integro-Differential Equations Using Generalized Spline Functions (Baghdad Science Journal, 2012)
This paper is dealing with non-polynomial spline functions "generalized spline" to find the approximate solution of linear Volterra integro-differential equations of the second kind and extension of this work to solve system of linear Volterra integro-differential equations. The performance of generalized spline functions are illustrated in test examples